A Novel Histological Study Evaluating the Combined Effect of Bovine-bone Graft and Royal Jelly on Socket Bone Healing in a Rabbit Model - Alhamrany, Shatha M.; Al-Ghaban, Nada M.H; Mutahar, Mahdi (Journal of the Faculty of Medicine Baghdad, 2025)
Background: The alveolar process, also called the alveolar bone, is a thickened ridge that contains the tooth sockets (dental alveoli) on the jaw bones that hold the teeth. After tooth extraction, several changes can occur in the alveolar process that may prevent or delay prosthodontic or other dental treatments. Recently, the Bovine-bone graft has been proposed to be applied in fresh extraction sockets to minimize the reduction in ridge volume. In recent experimental studies, Royal jelly has been shown to have antibacterial, antioxidant, antitumor, and anti-inflammatory properties, resulting in vascular dilatation and increased cell proliferation and differentiation. Objective: To evaluate the efficacy of Bovine-bone graft and Royal Jelly separately and in combination on socket bone healing. Methods: Forty-eight rabbits were divided into four groups (Control, Royal Jelly (RJ), Bovine-Bone Graft (BG), Combination). The results were studied histologically after two and four weeks, postoperatively. A histological examination was performed under a light microscope for the section stained with hematoxylin and eosin (H&E). The study was conducted between November 2023 and ended in September 2024 in the laboratory of Histology in the College of Dentistry / University of Baghdad. Results: In the RJ group, the socket area showed the formation of new bone trabeculae, lined by osteoblasts and osteocytes, with higher mean values than in other groups. Histomorphometric analysis revealed that RJ-treated sockets exhibited significantly higher trabecular bone area (p<0.001) and osteoblast/ osteocyte counts compared to the BG and Control groups. Conclusion: The use of Royal Jelly separately or in combination with Bovine-bone graft is more beneficial than the Bovine-bone graft alone, for socket bone healing.